Nonlinear modelling of a fishing boat and Fuzzy Logic Control design for electro-hydraulic fin stabilizer system - Alarcin, Fuat (SPRINGER, 2014)
The aim of this study is to decrease a fishing boat's nonlinear roll motion using Electro-Hydraulic (EH) fin roll stabilizer, which is adversely affected by disturbing hydrodynamic forces, by applying fin roll stabilizer. By Fuzzy Logic Control (FLC) method, the fishing boat rolling was examined considering initial conditions. Besides, NACA 0015 model was utilized for the fin roll stabilizer and flow analysis was conducted by CFD method. According to the simulation results, FLC algorithms were rather more efficient than PID (Proportional-Integral-Derivative) in the EH fin roll stabilizer system.
Keywords: Nonlinear roll motion; Electro-hydraulic fin stabilizer; Fuzzy control; PID control; Engineering; Mechanics